The histological changes in the bone marrow in an experimental lesion of the bone - Мазуркевич, А. Й.; Малюк, М. О.; Харкевич, Ю. О.; Савчук, Т. Л. (Scientific Progress & Innovations, 2017)
We investigated the histological changes in the bone marrow in experimental damaged bone tissue. Analysis of histological changes in the bone marrow confirms the pattern and character of development of reparative osteogenesis. We established that mechanical trauma to the bone causes severe reactions at the site of the defect, not only from the bone tissue, and bone marrow. It was also found that with 14 day intensive osteogenesis. The obtained data can be used to develop stimulation methods and means of preventing complications in the restoration of bone tissue after injury.